Kajian Sistematis Integrasi Optik Lokal Yogyakarta dengan E-Commerce Tokopedia dan Shopee - Kusumo, Sri Wahyu Budoyo; Wicaksono, Ardhitya Furqon; Wibowo, Arraywed Yudita (JURNAL MANAJEMEN DAN BISNIS, 2025)
Digital transformation driven by the development of information technology has affected various sectors, including the optical business. In Yogyakarta, a city with rapid growth of optical MSMEs, the utilization of e-commerce platforms such as Tokopedia and Shopee is still not optimal. In fact, the adoption of marketplaces has the potential to expand market reach and increase competitiveness. This study aims to examine the readiness and challenges of adopting digital technology in local optical businesses through the Systematic Literature Review (SLR) approach with the PRISMA protocol. A total of 25 relevant articles were selected from the Google Scholar, Garuda, DOAJ, and Scopus databases based on the inclusion criteria: publications in 2018–2024 and focusing on the digitalization of health MSMEs, e-commerce, and optical business practices in Indonesia, especially the Yogyakarta region. The results of the study showed that 87% of the literature supports the benefits of e-commerce integration for market expansion and improving customer experience. However, only around 12% of local opticians have implemented digital strategies optimally, especially in utilizing marketplace features such as chatbots, stock integration, and Official Stores. The main challenges include limited digital literacy of the workforce, inefficient logistics, and unsynchronized online health service regulations. This study concludes that structural readiness and increasing digital competence are the main prerequisites in optimizing the transformation of the optical business through e-commerce. As a recommendation, digital literacy training, marketplace integration workshops, and support for incentive policies from local governments are essential. This study also offers a conceptual model of three pillars of integration: digital products, marketplace interactions, and online-offline service synchronization as the basis for a post-pandemic local optical digitalization strategy.